2018
DOI: 10.1002/acr.23451
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin K Status Combined With Vitamin D Status and Lower‐Extremity Function: A Prospective Analysis of Two Knee Osteoarthritis Cohorts

Abstract: Sufficient vitamin K status combined with sufficient vitamin D status was associated with better lower-extremity function in 2 knee OA cohorts. These findings merit confirmation in vitamin K and D co-supplementation trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
(98 reference statements)
0
13
0
Order By: Relevance
“…So vitamin D supplementation could be used for knee OA pain. Vitamin D supplementation for six months reduced oxidative protein damage, decreased pain (VAS), improved quality of life, and improved grip strength and physical performance in osteoarthritis patients, and improves lower extremity functions ( Manoy et al, 2017 ; Shea et al, 2017 ). However Sanghi et al (2013) assert a reason for the positive effect of vitamin D, which in many studies only OA patients with insufficiency vitamin D, the group most likely benefit from supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…So vitamin D supplementation could be used for knee OA pain. Vitamin D supplementation for six months reduced oxidative protein damage, decreased pain (VAS), improved quality of life, and improved grip strength and physical performance in osteoarthritis patients, and improves lower extremity functions ( Manoy et al, 2017 ; Shea et al, 2017 ). However Sanghi et al (2013) assert a reason for the positive effect of vitamin D, which in many studies only OA patients with insufficiency vitamin D, the group most likely benefit from supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…However, both nutrients were not associated with gait speed. On the other hand, adequate vitamin K (≥ 90 µg/day for women or 120 µg/day for men) and D intake (≥ 600 IU for age < 70 years, ≥ 800 IU for age ≥ 70 years) were associated with overall 20-m gait speed and chair stand completion time, on follow-up, but not in the 400-m walk time [37]. In another study, subjects with vitamin K deficiency also showed higher pain scores on The Western Ontario McMaster Scale Scores, after 12 months follow-up study [25].…”
Section: Prospective Studiesmentioning
confidence: 94%
“…Therefore, long-term supplementation of vitamin K for preventing OA might be safe, but there is a paucity of trial data to support this claim. The effective dose of vitamin K in preventing OA remains elusive, but some data suggest that maintaining the circulating vitamin K concentration around 1.0 nmol/L is associated with better joint health [29,37].…”
Section: Perspectivesmentioning
confidence: 99%
“…Supplementation with vitamin K is used to treat and prevent osteoporosis and osteoarthritis in humans (Neogi et al 2006;Oka et al 2009;Misra et al 2013;Shea et al 2017). In Japan MK-4 is frequently used to aid in the prevention and treatment of osteoporosis with high doses of 45mg/day prescribed .…”
Section: Osteocalcin and Bone Metabolism And Diseasementioning
confidence: 99%
“…Vitamin K has been shown to play a vital role in bone development (Shea et al 2017). This role stems from its relationship to the bone protein, osteocalcin (Shea & Booth 2008).…”
Section: Introductionmentioning
confidence: 99%